2014
DOI: 10.1116/1.4890473
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoceria based electrochemical sensor for hydrogen peroxide detection

Abstract: Oxidative stress is a condition when the concentration of free radicals and reactive molecular species rise above certain level in living systems. This condition not only perturbs the normal physiology of the system but also has been implicated in many diseases in humans and other animals. Hydrogen peroxide (H2O2) is known to be involved in induction of oxidative stress and has also been linked to a variety of ailments such as inflammation, rheumatoid arthritis, diabetes, and cancer in humans. It is one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 45 publications
4
33
1
Order By: Relevance
“…Hz in the impedance data as discussed in our previous reports [39,58]. D a across the MCPs@GNR/electrolyte interface is found to be 3.3×10 -7 cm 2 s -1 which is observed to be apparently 1.5 times higher than 2.08×10 -7 cm 2 s -1 for GNR electrode and ~14 times higher than 2.4×10 -8 cm 2 s -1 for MCPs electrode (Figure 7b).…”
Section: Electrochemical Behaviour Of Mcps@gnr Nanocomposite Sensorsupporting
confidence: 72%
See 1 more Smart Citation
“…Hz in the impedance data as discussed in our previous reports [39,58]. D a across the MCPs@GNR/electrolyte interface is found to be 3.3×10 -7 cm 2 s -1 which is observed to be apparently 1.5 times higher than 2.08×10 -7 cm 2 s -1 for GNR electrode and ~14 times higher than 2.4×10 -8 cm 2 s -1 for MCPs electrode (Figure 7b).…”
Section: Electrochemical Behaviour Of Mcps@gnr Nanocomposite Sensorsupporting
confidence: 72%
“…Consequently, ion diffusibility in vertical as well as horizontal direction is enhanced [59]. Peak currents, I pa and I pc are linearly proportional to the scan rate (Inset Figure 7e) with I pa /I pc ratio about unity in the range from 5 to 200 mVs -1 (I pa R 2 =0.9963; I pc R 2 =0.9976) reflecting surface-controlled reversible process [58]. It is observed that both anodic peak (E pa ) and cathodic peak (E pc ) shift slightly to the positive and negative direction respectively.…”
Section: Electrochemical Behaviour Of Mcps@gnr Nanocomposite Sensormentioning
confidence: 95%
“…1 Its unique properties are attributed to the surface Ce 3+ ions, providing a redox couple with Ce 4+ . 2,3 The Ce 3+ sites are accompanied by oxygen vacancies near the surface. Therefore, small CeO2 NPs of several nanometers possess enhanced activities due to a large surface-to-volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Apparent diffusion coefficient (Da) of electrolyte ions is estimated from the diffusion controlled regime (ΔZim/ΔZre ≈ 1) which lies in the frequency range ~ 8 Hz -0.8 Hz of the impedance data. Da across the electrode/electrolyte interface is calculated from the slope of plot |Z| vs ω -1/2 as previous reports [28,29] and is found to be 2.25x10 -8 cm 2 /s (Fig. 3d).…”
Section: Resultsmentioning
confidence: 99%